OXIDATION KINETICS OF MANGANESE (II) IN SEAWATER AT NANOMOLAR CONCENTRATIONS - von Langen P.J.; Johnson K.S.; Coale K.H.; Elrod V.A. (My University, 1997)
Manganese oxidation rates were determined at low (#20 nM) concentrations in seawater by measuring dissolved manganese (Mn(II)) using flow injection analysis with chemiluminescence detection. Mn(II) was measured in samples that had been filtered (0.2 μm) and kept in the dark under controlled temperature and pH conditions for time periods up to 6 months. Eight 9 L carboys with mean pH values ranging from 8 to 8.7 were held at 25°C, another carboy (pH = 9.32) was kept at 5°C. Oxidation followed the Morgan (1967) homogeneous rate equation (d[Mn(II)]/dt = k1 [O2] [OH-]2 [Mn(II)]). The mean rate constant k1 = 1.7 +/- 0.7 x 1012 M-3 d-1 (95% CI), determined using hydroxide ion activities determined with pH measurements on the NBS scale, was in agreement with work by Morgan (1967; k1 = 4 x 1012 M-3 d-1) and Davies and Morgan (1989; k1 = 1.1 x 1012 M-3 d-1) in dilute solutions. The rate constant at 5°C was 1.3 +/- 0.3 x 1012 M-3 d-1. If free hydroxide concentrations (based on the free proton pH scale) are used, then the rate constant at 25°C was k*1 = 0.34 +/- 0.14 x 1012 M-3 d-1.Autocatalytic increases in Mn(II) oxidation rates, as predicted by a heterogeneous reaction mechanism (Morgan, 1967) (d[Mn(II)]/dt = k'2[Mn(II)] [MnO2]) were not observed, indicating that the homogeneous reaction dominates Mn(II) oxidation at low nM concentrations in seawater. Bacteria were enumerated by 4',6-diamidino-2-phenylindole (DAPI) staining during the experiments. No significant correlation between bacterial concentrations and Mn(II) oxidation rates was found.